Relationship of Sustainability Disclosure to Market Value of Enterprises of Companies Listed on The Stock Exchange of Thailand : SET100 - Manrai, Nualsiri; Chaweerak, Aukkharadech; Akarak, Panchat (Vocational Education Central Region Journal, 2025)
The objective of this research is to study the relationship between sustainability disclosure and market value. of companies listed on the Stock Exchange of Thailand, SET100 group, during the period 2021-2023, for 3 years. The total number of companies used in the study is 92 companies, totaling 276 data. The independent variable is environmental sustainability information disclosure. Disclosure of social sustainability information and disclosure of corporate governance sustainability information. The dependent variable consists of enterprise value according to Tobin’ Q. The results of the study found that Sustainability disclosure Environmental aspect and corporate governance has a positive relationship with market value of enterprises. To provide information to shareholders and investors, they can use the results from this research to make investment decisions.